S37 Comparison of dynamic contrast enhanced MRI (DCE-MRI) parameters with integrated PET-CT and serum mesothelin in the baseline assessment of malignant pleural mesothelioma. (16th November 2010) - Hooper, C; Hall, D; Virgo, P; White, P; Darby, M; Hall, T; Braybrooke, J; Searle, J; Lyburn, I; Maskell, N
Abstract : Integrated PET-CT scans and serum mesothelin measurement have shown early promise in predicting prognosis and evaluating treatment response in malignant pleural mesothelioma (MPM) but may be less reliable with sarcomatoid histology or prior talc pleurodesis. Dynamic Contrast Enhanced-MRI (DCE-MRI) with pharmacokinetic analysis is a novel metabolic imaging modality providing a measure of tumour blood flow and angiogenesis. We prospectively examined the relationship between pharmacokinetic parameters on DCE-MRI with PET-CT, serum mesothelin and histological sub-type in MPM patients at diagnosis. Method: 30 pre-treatment patients with a histologically proven MPM underwent DCE-MRI and integrated PET-CT and serum mesothelin assay (MESOMARK) at a single visit. SUVmax and total glycolytic volume (TGV) were reported from PET-CT scans with TGV calculated using MIM software version 4.2.2 (MIMvista corp.). Gadolinium washout rate (GWR) on DCE-MRI was defined at a region of interest from a straight line fit to the kinetic curve data (CAD software—ViewForum R6.3 V1L3, Philips Medical Systems) between peak enhancement in the first 2 min and the last data point. Results: 70% (21/30) epithelioid and 30% (9/30) sarcomatoid histology. 43% (13/30) had undergone prior talc pleurodesis. Histology did not statistically significantly affect SUVmax, TGV or GWR. Serum mesothelin was significantly greater in the epithelioid group (3.2 nM/l (2.0, 6.3) vs 0.6 nM/l (0.5, 0.8) p<0.001). There was no significant difference in mesothelin, SUVmax, TGV or GWR between talc pleurodesed and non-pleurodesed patients in the whole group, but in the epithelioid sub-group there was a trend to significantly higher TGV with talc pleurodesis (talc: 2799 (1931, 11257) no talc: 955.5(146.8, 2354) p=0.053) that was not observed with GWR (p=0.4179). While SUVmax strongly correlated to TGV (r=0.725, p<0.001), there was no correlation between GWR and TGV (r=0.203, p=0.282) or between mesothelin levels and any of the imaging values. Conclusion: Metabolic imaging has been proposed as an important component of the assessment and management of patients with malignant pleural mesothelioma. Gadolinium washout rate on DCE-MRI may be less sensitive to talc pleurodesis than PET-CT parameters and MRI is a cheaper, more readily available modality that involves shorter patient appointment times, warranting further study in MPM prognostic evaluation and treatment response monitoring.